Use of At-Home Medical Tests Among Older US Adults: A Nationally Representative Survey - Joshua B. Rager MD, MA, MS; Matthias Kirch MS; Dianne C. Singer MPH; Erica Solway PhD, MSW; Preeti N. Malani MD, MSJ; J. Scott Roberts PhD; Jeffrey T. Kullgren MD, MPH, MS (SAGE Publishing, 2024)
The availability of direct-to-consumer, at-home medical tests has grown over the last decade, but it is unknown how frequently older adults purchase at-home tests, how they perceive such tests, and how interested they are in using at-home tests in the future. We conducted a cross-sectional, nationally representative survey of non-institutionalized US adults aged 50 to 80 about their previous use of, perceptions of, and future intentions to use at-home medical tests. We found that nearly half of older adults (48.1%) have purchased an at-home medical test (95% CI 45.2%-51.0%), including 32.0% (95% CI 29.3%-34.8%) who purchased a COVID-19 test, 16.6% (95% CI 14.7%-18.7%) who purchased an at-home DNA or genetic test, 5.6% (95% CI 4.5%-7.0%) who purchased a screening test for cancer, and 4.4% (95% CI 3.4%-5.6%) who purchased a test for an infection other than COVID-19. Compared with White, non-Hispanic adults, Black, non-Hispanic adults were less likely to have purchased an at-home test (35.5% vs 49.6%, P  < .01). Those with a college degree and those with an annual household income greater than $100K were more likely than others to have purchased at-home tests (55.5% vs 42.0%, P  < .01; 60.6% vs 39.0%, P  < .001, respectively). Most older adults had positive perceptions about at-home tests and expressed interest in using at-home tests in the future. At-home medical testing is now common among older adults. Clinicians should be familiar with different tests that patients can purchase and be prepared to discuss the potential advantages and disadvantages of at-home testing.